Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan Pada Restoran Tradisional Di Kota Bandung - Hanifah, Mira (JURNAL DESTINASI PARIWISATA, 2024)
The ever-changing business environment demands constant adaptation. Businesses that fail to understand and interact with their customers effectively risk losing their loyalty and patronage. One strategy that companies can implement to combat this is to enhance the quality of their service offerings. This research aims to investigate the influence of service quality on customer loyalty in traditional restaurants within Bandung city. The employed research method is quantitative, utilizing purposive sampling techniques. Data collection was conducted through online questionnaires distributed to customers who have previously visited traditional restaurants in Bandung. A total of 50 respondents participated in this study. The research findings indicate a significant positive influence of service quality on customer loyalty in traditional restaurants within Bandung city. The calculated t-value (11.256) exceeds the t-table value (2.010), resulting in a correlation coefficient (r) of 0.852. This demonstrates a reasonably strong relationship between service quality and customer loyalty in traditional Bandung restaurants. The coefficient of determination (R Square) value of 0.725 suggests that service quality explains 72.5% of the variation in customer loyalty, while the remaining 27.5% is attributed to factors not examined within the scope of this study. The research concludes that customer loyalty is also influenced by the factor of staff friendliness and staff solution resolution. Keywords: interaction, relation, tourism, loyalty, management